Mindset and Self-Efficacy as Determinants of Grit: Evidence from a Vocational High School Context - Muhamad Takiuddin; Desi Ariska; Muhamad Zainul Majdi (AL-ISHLAH: Jurnal Pendidikan, 2025)
Grit is a crucial psychological trait for vocational high school students, contributing to their persistence and success in learning and future employment. This study investigates the influence of mindset and self-efficacy on students’ grit. A quantitative ex post facto design was used with a sample of 80 students from SMK Negeri 2 Selong, selected through simple random sampling based on Taro Yamane’s formula. Data were collected using validated Likert-scale instruments for mindset, self-efficacy, and grit. Multiple regression analysis was conducted using SPSS to assess the relationship and contribution of the independent variables to grit. The results indicated that mindset had a significant positive relationship with grit (p 0.05), while self-efficacy did not show a significant influence (p = 0.231). The model explained 22.7% of the variance in grit. The effective contribution of mindset was 23.9%, while self-efficacy had a negative contribution (-1.2%), suggesting that mindset played a more substantial role in predicting grit among students. The relative contribution was 105% for mindset and -5% for self-efficacy, indicating possible multicollinearity or suppression effects. The findings highlight the importance of fostering a growth mindset to enhance grit in vocational students. While self-efficacy is commonly associated with persistence, its non-significant result here suggests that other contextual or psychological factors may moderate its impact. Future research should explore additional variables that influence grit and validate these findings across diverse student populations.